Employability and skills of higher education graduates: A Portuguese study - Cassio Rolim; Maria de Lourdes Machado-Taylor (European Regional Science Association (ERSA), 2016)
One important conquest of the XXI Century is the fact that Higher Education is available for a large amount of the population. This is important also for countries and regions due to the emphasis on the development of literature on knowledge and innovation as a motor for the development of modern economies. However, it is a paradox that one of the biggest problem nowadays is the unemployment among graduates. The universities from developed countries, particularly in the European Union never formed so many young as now but they remain unemployed. On the other hand, the enterprises hardly meet new employees with the necessary skills. Clearly, there appears to be a mismatch between the training that these young people acquire at the universities and the skills demanded by the companies and the labour market in general. The literature on this topic discusses the skills that these graduates will need to meet the requirements of the labour market. Divided into professional and technical (hard) skills and interpersonal communication (soft) skills. The first are those basic skills in the area of technical training. For example, in Economics, fundamental knowledge of economic theory, econometrics, social and historical context for understanding the economic process, and so on. The domain of these competences is part of the educational process acquired in higher education institutions, (HEIs). The second, the soft skills, as related to the personal qualities of interpersonal communication, were initially considered skills acquired outside of the school system. The current state of the debate considers that they should be acquired at school by the use of new pedagogical methodologies such as Problem Based Learning (PBL) This paper is a report of the first methodological review of a research project that aims to replicate in Portugal a study already carried out in the European Union, considering the constraints of the employability of graduates from HEIs, analysed from the perspective of employers. The sample in Portugal will choose among 1000 employers from selected economic sectors at different regions. Two special features accentuate his originality. The first is the emphasis on the perspective of the employers, rarely found in similar jobs. The second is the methodology that enhances the selection and contracting processes rather than simply inquires employers about the ideal profile demanded of a graduate. The first stage of this process is a simulation of a contracting process of a newly graduate for a full-time post in the company, with the expectation that this professional will have a career in the company. After a selection based on the features available in their Curriculum Vitae, the chosen candidates goes to a second stage. At this stage will be another simulation of an interview that will select a single candidate for the post. The outcomes of this project will give important information about what employers expected, in fact, from the HEI's graduates. It will be helpful also for the debate about improvements in the Portuguese higher education policy.
Keywords: R11; I23; I25; 330; Employability; Soft Skills; Higher Education